Improving mathematical problem solving ability of senior high school students through learning with metacognitive scaffolding approach - R Gusmiyanti; S Suhendra; E Nurlaelah (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
Problem solving is an important skill that need to be developed in mathematics education. Sharpening problem solving skills enablestudents to improve their ability to analyze and train students to think creatively. However, in reality the students were less facilitated in sharpening the development of problem-solving abilities. Consequently, the problem solving ability of students has not been satisfactory. One of the efforts that could be done to overcome his problem is applaying metacognitive scaffolding approach in learning. Metacognitive scaffolding is an approach that emphasizes self-monitoring capability. Monitoring is the way a person monitors what students know and do not know. While scaffolding is a help given by the teacher to the students. When students feel able to work independently, teachers slowly reduce scaffolding. This study aimed to determine whether the approach of metacognitive scaffolding could improve problem-solving abilities. Thereserach applied quasi experimentresearch with Nonequivalent Control Group Design. This research took place in one of State Senior High School in Padang Pariaman District, West Sumatera. The results show that metacognitive scaffolding approach could improve mathematical problem solving ability.